y=x^2 + x - 2
x + y = 1
Replace y in the second equation:
x + x^2 + x -2 = 1
Simplify:
x^2 + 2x -2 = 1
Subtract 1 from both sides:
x^2 + 2x -3 = 0
Factor:
(x-1) (x+3) = 0
Solve for both x's:
x = 1 and x = -3
Now replace x in the second equation and solve for y using both x values:
1 + y = 1, y = 0
-3 + y = 1, y = 4
Now you have (1,0) and (-3,4) as solutions for (x,y)
XY = x times y:
1 x 0 = 0
-3 x 4 = -12
The answer would be -12
Answer:
95 degrees.
Step-by-step explanation:
Their sum is 180. You will subtract 85 to get the other half of the whole.
180 - 85 = 95
The other angle is 95 degrees.
I believe one
is named congruent triangle
not sure for the other one
Answer:
Step-by-step explanation: